Decolonising sambo : transculturation, fungibility and black and people of colour futurity - Tate, Shirley Anne (Bingley, U.K. : Emerald Publishing Limited, 2019)
This book decolonises 'sambo' as racialised knowledge, power, being and affect to unsettle its place in the history of 'mixed race' and racialised naming forged through settler colonialism which in its afterlife continues to haunt our contemporary period through national commemoration, cultural production and markets in contemptible collectibles.
Prelims -- Chapter 1: Introduction: Sambos Social Etymology and White European Settler Colonial Transculturation -- Chapter 2: Naming: The Fungibility of Subjection, Transculturation and Colonial Inferiority -- Chapter 3: Consuming Sambo and Necropolitical Love/Hate: Humour, Childrens Books and Sweets -- Chapter 4: Biopolitics and Racialising Assemblages: Australian Colonial Breeding Out/In and the Nation -- Chapter 5: Contemptible Commemoration: Racial Capitalism and Love/Care for Long Dead Sambo -- Chapter 6: Post-Race Racial Libidinal Economies: Markets and Contemptible Collectables -- Chapter 7: Racisms Affects in Scandals Refusals: Transracial Intimacy, Post-Race Power and the Love of the American People -- Chapter 8: Conclusion: Black/People of Colour Futurities Decolonising Mind, Affect, Being and Power -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record.
Keywords: Colored people (South Africa); Race discrimination; Blacks -- Study and teaching; Social Science, Black Studies (Global); Social & cultural anthropology, ethnography